Metodologia de avaliação multicritério da vulnerabilidade à desertificação no Semiárido - Araújo, Flávia Telis de Vilela (2014)
This work aims to construct a methodology for multicriteria decision support (AMD) to estimate vulnerability to desertification in the Brazilian semiarid region, depending on anthropogenic pressures related to economic exploitation of the region. Desertification, understood as a phenomenon resulting from the critical areas of environmental degradation in arid, semi-arid and dry sub-humid climate, contributes to increasing local vulnerability, a situation which was defined as low-level equilibrium. Rainfed and irrigated, livestock, exploitation of forest resources, mining, agribusiness and exploitation of water resources, and estimated the environmental impacts related to increased vulnerability to desertification agriculture: the economic activities most representative were selected. Selected for the assessment of impacts criteria consisted of biotic, abiotic and anthropogenic, inserted into a decision matrix. In the impact assessment experts (decision makers), who attributed values ​​based on your preferences in order to use up the multi-attribute utility theory (MAUT) and modeling functions for risk estimation in Excel spreadsheets were consulted. Scenarios were considered low and high natural vulnerability to desertification, and the presence or absence of mitigating the development of economic activities measured. The methodology was simple to apply and can be used in other environmental assessments. The evaluation results validated the proposed methodology. To minimize the vulnerability to desertification measures of adaptation, mitigation and combat were studied, aiming to increase the resilience of environmental systems in order to reduce vulnerability to the phenomenon of desertification.